BIOMONITORING OF MACROINVERTEBRATE DIVERSITY AS AN INDICATOR OF POLLUTION IN DEKET RIVERS LAMONGAN REGENCY - Saad, Moch; Shaleh, Fuquh Rahmat; Mas'ud, Faisol (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2025)
Macroinvertebrates are aquatic organisms that live at the bottom of the water, have relatively slow movements, and have a relatively long life span so that they can respond to river water conditions, changes in water quality, and the substrate in which they live significantly affecting their composition and abundance. This research aims to determine the diversity value, macroinvertebrate dominance, and the river water quality based on the Family Biotic Index (FBI) in the Deket River, located in the Lamongan Regency. The sampling method used a purposive sampling method, sampling was carried out at 3 stations and 4 replications, macroinvertebrates were taken using an Ekman grab tool, and river water quality values were measured using the family biotic index (FBI). Based on the research results, there is a moderate pollution level in the Deket River, as shown by the results of the FBI value with the water quality category being rather poor, with a high pollution level with a large population. The diversity index value for macroinvertebrates in the Deket River is between 1.27 and 1.57, included in the medium category. Meanwhile, the macroinvertebrate dominance index value in the Deket River is relatively poor.